PERUBAHAN ORGANISASI KECAMATAN PASKA REFORMASI: DISCOURSE ANALYSIS BERDASARKAN PARADIGMA NEW PUBLIC SERVICES - Ramdani, Rijal; Al-Hifdhi, Hefi (Universitas Riau Kepulauan, 2024)
Abstract: The sub-district organization (Kecamatan) in Indonesia plays an essential role as the forefront of local governments in providing service delivery for the citizens. Following the New Public Service’s (NPS) theory, this study aims to examine how have the sub-district roles changed after the political and bureaucratic reform in Indonesia. The study employed discourse analysis method that was used to observe how texts regarding the role and position of sub-district organizations had changed in the regulations. The data for this study was based on some regulations, namely 1) Law No. 32/2004, 2) Law No. 23/2014, 3) Government Regulation No. 19/2008, and 4) Government Regulation No. 17/2018. In this study, the NPS paradigm is understood as a new paradigm in public services where citizens are positioned as citizens who are actively involved and responsible in the policy formulation and public services. The study has found that both 1) Law No. 32/2004, 2) Law No. 23/2014, 3) Government Regulation No. 19/2008, and 4) Government Regulation No. 17/2018 have content that is close to the criteria of the New Public Service (NPS) paradigm. The results of cloud analysis also show that sub-district regulations after the Indonesian reformism have a commitment in positioning the sub-district organization as a public service delivery institution for the community. However, the regulations still are not sufficiently covered the essential role of individuals as citizens who can actively participate in the policy formulation and public service processes. Abstrak: Organisasi kecamatan memiliki peran penting sebagai ujung tombak bagi pemerintah daerah dalam memberikan pelayanan publik kepada masyarakat. Penelitian ini bertujuan untuk melihat bagaimana perubahan peran penting organisasi Kecataman setelah reformasi dengan menggunakan pendekatan paradigma New Public Services (NPS). Penelitian ini menggunakan metode discourse analysis yaitu suatu metode untuk melihat bagaimana teks mengenai peran dan kedudukan organisasi Kecamatan mengalami perubahan di dalam peraturan perundangan. Data pada penelitian ini didasarkan pada peraturan perundangan yaitu 1) Undang – Undang (UU) No. 32/ 2004, 2) UU No. 23/ 2014, 3) Peraturan Pemerintah (PP) No. 19/ 2008, dan 4) PP No. 17/ 2018. Di dalam penelitian ini, paradigma NPS dipahami sebagai paradigma baru di dalam pelayanan publik di mana warga Negara didudukan posisinya sebagai citizen, yang berperan aktif ikut terlibat dan bertanggung jawab di dalam proses perumusan kebijakan dan pelayanan publik. Penelitian ini menemukan bahwa baik UU. No. 32/ 2004, 2) UU No. 23/ 2014, 3) PP No. 19/ 2008, dan 4) PP No. 17/ 2018 muatannya sudah mendekati kriteria dari paradigma NPS. Hasil cloud analisis juga menujukan bahwa peraturan perundangan Kecamatan paska reformasi memiliki semangat kuat di dalam menempatkan organisasi Kecamatan sebagai institusi pelayanan bagi masyarakat. Akan tetapi peraturan perundangan tentang Kecamatan tersebut masih belum bisa meletakkan peran penting individu sebagai citizen yang bisa berperan aktif di dalam proses perumusan kebijakan dan pelayanan publik.